2020
DOI: 10.3892/ol.2020.11271
|View full text |Cite|
|
Sign up to set email alerts
|

Total flavonoids suppress lung cancer growth via the COX‑2‑mediated Wnt/β‑catenin signaling pathway

Abstract: The aim of the present study was to explore the anti-cancer effects of total flavonoids (TF) on lung cancer and to investigate the underlying mechanism. The inhibitory effect of TF on the proliferation of A549 cells in vitro was measured using an MTT assay. The apoptotic rate of TF-treated A549 cells was analyzed using flow cytometry and terminal deoxynucleotidyl transferase-mediated biotinylated UTP nick end labeling. Migration and invasion assays were performed to investigate the anti-migration effect of TF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The experimental results of cells and animal models have demonstrated that overexpression of COX-2 can inhibit tumor cell apoptosis, enhance cellular adhesion to achieve an invasive phenotype and promote tumor-induced angiogenesis (20,21). These theories have been confirmed in different types of tumors, including gastric (4), lung (22), pancreas (23), bladder (24), head and neck (25) and breast cancer (26). The present review discusses the effect of overexpressing COX-2 on the regulation of tumor growth and carcinogenesis.…”
Section: Roles Of Cox-2 In Cancermentioning
confidence: 92%
“…The experimental results of cells and animal models have demonstrated that overexpression of COX-2 can inhibit tumor cell apoptosis, enhance cellular adhesion to achieve an invasive phenotype and promote tumor-induced angiogenesis (20,21). These theories have been confirmed in different types of tumors, including gastric (4), lung (22), pancreas (23), bladder (24), head and neck (25) and breast cancer (26). The present review discusses the effect of overexpressing COX-2 on the regulation of tumor growth and carcinogenesis.…”
Section: Roles Of Cox-2 In Cancermentioning
confidence: 92%
“…The ability of A549 cells to proliferate was decreased by TF in a dose-dependent manner; however, this effect was reversed by activating Wnt signaling via COX-2. Additionally, animal studies revealed that TF therapy greatly slowed the growth of mouse tumors, with a tumor inhibition rate of 64.07%, and increased the survival time of the animals ( Han et al, 2020 ).…”
Section: Intervention Of Natural Products On the Canonical Wnt Pathwa...mentioning
confidence: 99%
“…Previous research found that therapy suppressed the Wnt and β‐catenin signaling pathway, which reduced cancer cell proliferation and elevated apoptosis. Additionally, antiproliferative and apoptotic activities are observed in the M. oleifera plant, which is related to the downregulation of the COX‐2, Wnt, and β‐catenin signaling pathways (Han et al., 2020).…”
Section: Mechanistic Role Of M Oleifera As An Anticancer Drugmentioning
confidence: 99%